Моніторинг запасів статичної стійкості енергосистеми на базі вимірів векторів напруги - Буткевич, О.Ф.; Левконюк, А.В.; Рибіна, О.Б. (Технічна електродинаміка, 2012)
The questions of construction and application of polynomial models (PM) for classification of power system operational conditions in depending on steady-state stability margins are considered. The measurements of voltage phasors are used as input data to PM. A comparison of PM and artificial neural networks by use a criterion of classification errors was realized.